Ресурси етнічного туризму України, пов’язані з вірменським народом - Орлова, М.Л.; Рєдіна, С.С.; Ярьоменко, С.Г. (Культура народов Причерноморья, 2014)
У статті коротко розглядається історія формування вірменської національної групи в
Україні. Представлено порівняння територіальної організації вірмен в межах України у XІ-XVIІІ
століттях та у сучасний період. Наведено коротку характеристику та картографовано ресурси
етнічного туризму України, пов’язані з вірменським народом. Виявлено, що у структурі даних ресурсів
переважають об’єкти релігійного характеру та пам’ятки, пов’язані з життям та творчістю відомих
представників вірменського етносу. В статье коротко рассмотрена история формирования армянской национальной группы в
Украине. Представлено сравнение территориальной организации армянв пределах Украины в XІ-XVIІІ
веках и на современном этапе. Коротко охарактеризованы и картографированы ресурсы этнического
туризма Украины, связанные с армянским народом. Выявлено, что в структуре данных ресурсов
преобладают объекты религиозного характера и памятки, связанные с жизнью и творчеством
известных представителей армянского этноса. Majority of Armenian lived in the Ukrainian territory in so-called «Armenian colonies» in period
from ХІ to XVIІІ centuries. There were separate quarters of the cities or villages in modern Lviv, Ivano-
Frankivsk, Chernivtsi, Ternopol, Khmelnitsky, Crimea and other regions. Compact residence and selfgovernment
favoured creation city planning, architectural, historical, cultural monuments that are possible to
use for ethnic tourism development. Religious objects prevail over ethnic tourism resources of the former
Armenian colonie, for example, Armenian cathedral architectural ensemble in Lviv, Armenian cloister Surb Hach near town Stariy Krym, Armenian churches in Ivano-Frankivsk, Gorodenka, Sniatyn, Chernivtsi, Lutsk,
Berezhany, Feodosiya, Yalta, Bilgorod-Dnistrovsky.
Contemporary Armenian people distribution all over the Ukraine significant differs from territorial structure of
Armenian colonies in ХІ-XVIІІ centuries. The greatest Armenian communities live in Donetsk, Kharkiv and
Dnipropetrovsk regions, communities in less number reside at Crimea, Odessa, Luhansk, Zaporizhzhya regions.
Modern ethnic tourism resources connected with Armenian national group here who was created material and
spiritual artefacts. There are churches, cultural centers, festivals, restaurant with Armenian cuisine. These
regions are promising for acquaintance with spiritual culture Armenian ethnos that are language, folklore,
customs, traditional handicrafts, dance and others.